Faktor – Faktor yang Berhubungan dengan Keberhasilan Induksi Persalinan pada Kehamilan Postterm di Rumah Sakit Rumah Sakit Datu Sanggul Rantau Tahun 2023 - Mawaddah Mawaddah; Erni Setiawati; Januarsih Januarsih (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
The incidence of caesarean section in Tapin Regency in 2022 will reach 55.3%, dominated by Datu Sanggul Rantau Regional Hospital at 42.5%. The aim of this research is to analyze factors related to the incidence of caesarean section at Datu Sanggul Rantau Regional Hospital in 2023. This research method is observational analytic with a case control design. The number of samples was 436 samples, with 218 caesarean section samples and 218 non-caesarean section samples, with the independent variables preeclampsia, premature rupture of membranes and fetal distress from the maternity register at Datu Sanggul Rantau Regional Hospital in 2023. The case sampling technique used purposive sampling and control sampling techniques. using simple random sampling. The statistical analysis used is chi square and odds ratio. The incidence of caesarean section was 43.9%; preeclampsia 17.4%; Premature rupture of membranes was 16.3% and fetal distress was 4.8%. There was a significant relationship between preeclampsia 26.1% (ρ-value = 0.001 < α = 0.05; OR = 3.708) and fetal distress 9.2% (ρ-value = 0.001 < α = 0.05; OR = 21.919 ) and the incidence of caesarean section, there is no relationship between premature rupture of membranes 16.3% (ρ-value = 0.069 > α = 0.05) and the incidence of caesarean section at Datu Sanggul Rantau Regional Hospital in 2023.